DEATH IN DENTAL MEDICINE- LITERATURE DATA - Bianca Hanganu; Andreea Elena Bîrlescu; Andreea Alexandra Hleșcu; Irina Smaranda Manoilescu; Simona Ionescu; Beatrice Gabriela Ioan (Romanian Society of Oral Rehabilitation, 2019)
Death and emergencies in dental medicine are rare events, occurring most frequently during dental surgery. Their occurrence is favored by various patient-related factors, physician-related factors, procedures applied and medical instruments used by the dentists. In this article, the authors analyze the factors that can lead to major medical emergencies and death in the current dental practice and identify possible solutions to avoid and/or solve them according to the literature. The authors conclude that even if the incidence of emergencies and death in current dental practice is reduced, the dentist and the whole team in his/her office must recognize these incidents and treat them correctly.